DETECTING AND PREVENTING BLACK HOLE ATTACKS ON WIRELESS SENSOR NETWORKS (INTERNATIONAL SCIENCE REVIEWS. NATURAL SCIENCES AND TECHNOLOGIES SERIES, 2024)
The protection of wireless sensor networks (WSN) is an urgent problem, since network nodes have low computing power, limited battery power and are located in unprotected places, and information is transmitted over wireless channels, any network disruption can lead to undesirable consequences. One of the common attacks against WSN is the Black hole attack. In this attack, the malicious host uses its routing technique to be able to advance in search of the fastest route to the host of the site or to the packet it wants to identify. This study analyzes the methods of protection in WSN against Black hole attacks. A method is shown of how a malicious node affects nodes in its transmission range.